Automated Ionogram Processing Shows Seasonal Variations in the Aurora Ionosphere - Reinisch,Bodo W; Tang,Jane; Hall,William N; Buchau,Jurgen (1982)
Automatic processing of digital ionograms from Goose Bay, Labrador (65 deg corrected geomagnetic latitude), permits fast evaluation of the diurnal and seasonal variations in the ionosphere. Ionogram data from 1980 are processed and displayed in ways that show the seasonal variations in foF2 and hminF. The effects of the mid-latitude trough that moves over the Goose Bay Station in the late evening are discussed. (Author)